Optoelectronics in machine vision-based theories and applications - Rivas-Lopez, Moises, 1960-; Sergiyenko, Oleg, 1969-; Flores-Fuentes, Wendy, 1978-; Rodríguez-Quiñonez, Julio C., 1985- (IGI Global, 2019)
"This book focuses on optoelectronic sensors, 3D & 2D machine vision technologies, robot navigation, control schemes, motion controllers, intelligent algorithms, agriculture applications and other vision systems. It covers topics such as applications of unmanned aerial vehicle, autonomous and mobile robots, medical scanning, industrial applications, agriculture, and structural health monitoring"--